Novel Supine Isometric Hamstring Test: A Reliability Study - Gorman, Barry T.; Kung, Stacey; Welch, Neil; Squillante, Antonio (International journal of kinesiology and sports science, 2024)
Background: Hamstring strain injuries are highly prevalent, particularly when the hamstrings are in a lengthened position; however, monitoring strength deficits and fatigue throughout a season is currently difficult due to a lack of practical, reliable tests that do not cause undue fatigue. Objective: The aim of the current study was to investigate the intersession reliability of a novel 90°hip: 40°knee isometric hamstring test (IHT) in the supine position. Methodology: This was a prospective, observational cohort study conducted on nine male participants (24 ± 3 years, 81.9 ± 6.4kg, 181.8 ± 5.3cm). Each participant completed two testing sessions of the 90°hip: 40°knee IHT using force platforms. Relative and absolute reliability of isometric peak force (IPF) were assessed using intraclass correlation coefficient (ICC) and coefficient of variation (CV%), respectively. Results: Relative reliability of the 90°hip: 40°knee IHT was considered “good” in the dominant limb (ICC = 0.92, Lower bound 95% Confidence Interval (CI) = 0.72) and “poor” in the non-dominant limb (ICC = 0.76, Lower bound 95% CI = 0.28). Absolute reliability was “acceptable” in both legs with 5.81% in the dominant limb and 9.65% in the non-dominant limb. Conclusion: The 90°hip: 40°knee IHT demonstrated moderate reliability overall, further research is required to discover the optimum IHT configuration which can be reliably executed at longer hamstring muscle lengths. This study provides foundational information for practitioners on a novel method of reliably testing hamstring isometric strength at longer muscle lengths.